2019
DOI: 10.1101/822445
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Actomyosin, vimentin and LINC complex pull on osteosarcoma nuclei to deform on micropillar topography

Abstract: Cell deformation occurs in many critical biological processes, including cell extravasation during immune response and cancer metastasis. These cells deform the nucleus, its largest and stiffest organelle, while passing through narrow constrictions in vivo and the underlying mechanisms still remain elusive. It is unclear which biochemical actors are responsible and whether the nucleus is pushed or pulled (or both) during deformation. Herein we use an easily-tunable poly-L-lactic acid micropillar topography, mi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…[50] Furthermore, it was shown that when nesprins were knockdown in osteosarcoma cells, their nuclear deformability was decreased which proved the essential role of nesprins in actomyosin contractility and nucleo-cytoskeletal connections. [51] In summary, based on the results and the literature data, we confirm that in addition to the actin cytoskeleton, nuclear envelope protein Lamin A/C and LINC protein Nesprin-2 have fundamental roles in nuclear localization and in intercellular interactions between inner nuclear and outer cytoskeletal components of the cells.…”
Section: Expression Of Lamin A/c and Nesprin-2 Before And After Drug supporting
confidence: 78%
See 1 more Smart Citation
“…[50] Furthermore, it was shown that when nesprins were knockdown in osteosarcoma cells, their nuclear deformability was decreased which proved the essential role of nesprins in actomyosin contractility and nucleo-cytoskeletal connections. [51] In summary, based on the results and the literature data, we confirm that in addition to the actin cytoskeleton, nuclear envelope protein Lamin A/C and LINC protein Nesprin-2 have fundamental roles in nuclear localization and in intercellular interactions between inner nuclear and outer cytoskeletal components of the cells.…”
Section: Expression Of Lamin A/c and Nesprin-2 Before And After Drug supporting
confidence: 78%
“…The reason of the loss of deformation can be explained with the need of actomyosin contractility for the movement and dislocation of the cells and their nuclei. [49][50][51] Lamin A/C and Nesprin-2 directly interact with actin filaments of the cells. CytoD caused the disruption of actin filament formation by inhibiting their polymerization, and therefore, cells lost actomyosin contractility, the transfer of mechanobiological stimuli is hampered and therefore, deformability is decreased.…”
Section: Expression Of Lamin A/c and Nesprin-2 Before And After Drug mentioning
confidence: 99%
“…Defective nuclear mechanosensing was evidenced by downregulation of Lamin A/C mRNA expression and corresponded to up-regulated HDAC mRNA expression and lower histone acetylation, thereby suggesting reduced bone regenerative capacity. The cytoskeleton, LINC complex, and the physical attachment to nuclear lamins have been shown to be highly important in nuclear integrity, chromatin remodeling, and subsequent differentiation or cell reprogramming (34,35). Multiple mechanisms have been suggested for Lamin A/C contribution to transcriptional changes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely known that 2D geometry can affect diverse cellular responses such as cell shape, proliferation, differentiation, mechanoresponsive marker expression, and underlying mechanism has been suggested that confined adhesive area which can be tuned by geometry of 2D patterns cause interfacial tension at the boundary [ 6 , 12 ]. As both topography and adhesiveness of the surface may play essential roles in cellular behavior [ 43 ], we treat the whole surface of the 3D geometry to be adhesive so that we can elucidate the roles of 3D geometry independent of chemical adhesiveness.…”
Section: Discussionmentioning
confidence: 99%